Working Mechanisms and Structure Engineering of Renewable Biomass‐Derived Materials for Advanced Lithium‐Sulfur Batteries: A Review. Issue 1 (10th November 2021) - Tian, Xiaohui; Yan, Chenzheng; Kang, Junbao; Yang, Xiaoya; Li, Quanxiang; Yan, Jing; Deng, Nanping; Cheng, Bowen; Kang, Weimin
Abstract: Lithium‐sulfur (Li−S) batteries have attracted attention in the field of energy storage due to their high energy density and theoretical capacity. However, there are still some obstacles to achieve commercial applications such as large volume expansion of sulfur, low electrical conductivity, the growth of lithium dendrites, and the polysulfide shuttle effect. Through continuous research on Li−S batteries, renewable biomass materials have been discovered by scholars and scientists due to their sustainable development, low cost, and extensive sources. The results showed that renewable biomass‐derived carbons had outstanding advantages such as high specific surface area and large pore volume, as well as inherent heteroatom doping after being applied to Li−S batteries, which had a significant effect on improving the electrochemical performance. This Review summarizes the research progress of Li−S batteries in renewable biomass materials in recent years, starting from three aspects: biomass carbon‐sulfur composite cathodes, biomass modified separators, and biomass independent flexible carbon interlayers. Firstly, the Review summarizes its physical barrier and adsorption mechanism (the effect of various porous structures), chemical reaction and adsorption mechanism, catalysis and conversion mechanism. Then, it classifies materials based on the source of renewable biomass as well as elaborating and analyzing the structures, mechanism, and performance among them. Finally, the Review summarized the shortages in this field, as well as the challenges and opportunities faced. The authors hope that this Review will have a certain reference value for the development of various biomasses for high performance Li−S batteries, and will inspire more scholars to devote themselves to the research of biomass materials for Li−S batteries. Abstract : Far and wide : A broad overview of biomass‐derived carbon materials in lithium‐sulfur batteries. Physical and chemical adsorption and catalytic mechanisms as well as advantages and disadvantages of biomass materials in lithium‐sulfur battery applications. Future development trends are also proposed.